Recent advances in law library services in Nigeria in the 21st century (2017)
This paper focused on ways by which law library services in Nigeria can be enhanced in the 21st century judging by the recent advances in the technological innovations that can be deployed to improve services. The objective was borne out of the observed low patronage of law libraries, moribund techniques and methods of rendering services and attitudes of law library staff to clients. The methodology was of qualitative type perusing literature on subject matter to get the general overview of the concept of law library services in the 21st century. The paper posited that information and communication technology adoption, extension of law library opening and closing hours and resource sharing through consortium will enhance improved law library services. The paper however concluded that the traditional library services such as collection of physical books should not be substituted with electronic resources rather there should be hybrid librarianship.